Efficacy of ormeloxifene in comparison to norethisterone in the management of abnormal uterine bleeding - Srinivasan, Suguna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Abnormal uterine bleeding (AUB) is the most common complaint worldwide. In India, most of the women present with menorrhagia and majority of them are anemic and require medical management to avoid its consequences. Hence this study is done to compare the efficacy of ormeloxifene with norethisterone in women presenting with AUB. Methods: In this study 61 women suffering from AUB were included. This prospective randomized double blinded study was done on women between the age group of 19-45 years and were allocated randomly into two groups, one group was given ormeloxifene and the other was given norethisterone for a period of 3 months. Haemoglobin levels, endometrial morphology on ultrasound were assessed before and after the treatment in both the groups. Results: It is observed in our study, that both ormeloxifene and norethisterone reduced menorrhagia. The rise in hemoglobin concentration was significantly more with ormeloxifene than norethisterone (8.3 g/dl to 10.3 g/dl versus 9.0 g/dl to 10.4 g/dl). In our study, the significant reduction in the endometrial morphology was more with ormeloxifene than norethisterone (9.3 mm to 7.8 mm versus 8.3 mm to 7.2 mm). Conclusions: Ormeloxifene is a new modality drug and is found to be a better option in reducing menorrhagia compared with norethisterone in respect to a greater success rate, better compliance and cost effectiveness. Hence our study concludes ormeloxifene as a better choice over norethisterone in the treatment of AUB.